Big data analytics for Internet of things - Saleem, Tausifa Jan; Chishti, Mohammad Ahsan (John Wiley & Sons, Inc., 2021)
"Big Data Analytics is a briskly expanding research area spanning diverse fields. The efficacy of Big Data Analytics is found mainly in the domain of Internet of Things (IoT). The number of IoT devices is anticipated to amount to several billion in the next few years. This unpredictable growth in the number of devices connected to IoT and the exponential rise in data consumption manifest how the expansion of big data seamlessly coincides with that of IoT. The main objective of Big Data Analytics in IoT is to identify trends in the data, extract concealed information and to dig out valuable information from the raw data generated by IoT systems. This is crucial for dispensing elite services to IoT users. In this regard, investigating the recent technological advancements in the said area becomes indispensable."- Resumé vydavatel
Keywords: big data; internet věcí; Internet of things; elektronické knihy; electronic books